2004
DOI: 10.1111/j.1440-169x.2004.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

CDK1/cyclin B regulation during oocyte maturation in two closely related lugworm species, Arenicola marina and Arenicola defodiens

Abstract: The molecular mechanisms underlying oocyte maturation in the annelid polychaetes Arenicola marina and Arenicola defodiens were investigated. In both species, a hitherto unidentified hormone triggers synchronous and rapid transition from prophase to metaphase, a maturation process which can be easily reproduced in vitro . Activation of a roscovitine-and olomoucine-sensitive M-phase-specific histone, H1 kinase, occurs during oocyte maturation. Using affinity chromatography on immobilized p9CKShs1 , we purified C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…MPF is a complex of two proteins, a regulatory component called cyclin B and the catalytic component protein kinase known as cyclin dependent kinase, Cdk1 (Yamashita et al 1992;Chausson et al 2004). Using mouse anti-cyclin monoclonal and anti-PSTAIRE antibodies we initially confirmed the presence of a 50 kDa cyclin B and a conserved p34Cdk1 protein in the oocyte extract of Catla catla as in our previously studied carps.…”
Section: Discussionmentioning
confidence: 99%
“…MPF is a complex of two proteins, a regulatory component called cyclin B and the catalytic component protein kinase known as cyclin dependent kinase, Cdk1 (Yamashita et al 1992;Chausson et al 2004). Using mouse anti-cyclin monoclonal and anti-PSTAIRE antibodies we initially confirmed the presence of a 50 kDa cyclin B and a conserved p34Cdk1 protein in the oocyte extract of Catla catla as in our previously studied carps.…”
Section: Discussionmentioning
confidence: 99%
“…It has now been demonstrated that sea urchin embryos exposed to decadienal during early ontogeny are unable to activate the G 2 -M phase promoting-complex cyclin B-Cdk1 despite an accumulation of cyclin B [ 107 ]. The G 2 -M phase promoting-complex is also essential for oocyte maturation in several marine invertebrates [ 108 ]. It is therefore likely that decadienal is acting against the maturation-promoting-complex in oocytes of A. rubens and probably copepods, thereby initiating a terminal cellular response.…”
Section: Gametogenic Effectsmentioning
confidence: 99%
“…MPF is responsible for controlling meiotic reinitiation, and in healthy oocytes, is present in a pre-MPF form awaiting activation through phosphorylation (Paterson et al, 1999;Chausson, et al, 2004). The observations suggest that eventually the checkpoint at the start of meiosis may be "overrun", and despite the absence of the correct cue for development, namely fertilisation, re-initiation of meiosis can still occur.…”
Section: Discussionmentioning
confidence: 87%